Strong and weak points in competence - based training according to Spanish Higher Education graduates - Andrea Conchado Peiró; José Miguel Carot Sierra (Universitat Politècnica de València, 2013)
The objective of this study is to analyze from a descriptive point of view the competences considered by higher Education graduates as strengths or weaknesses in their studies. This objective arises from the growing importance that competences have acquired during the preceding years due to the adaptation process of university degrees to the European Higher Education Area. With this aim in mind some specific results, based on a sample of 5,474 Spanish university graduates and thirteen study programs, are described. Data were obtained from the research project REFLEX «The Flexible Professional in the Knowledge Society: New Demands on Higher Education in Europe». Universities from fourteen European countries and Japan participated in the project, and one of the aims was the analysis of competencies in Higher Education. Results describe how graduates point out to competences related to traditional teaching methods as strengths of their studies, such as knowledge of the field of study, ability to analyze and learn and teamwork, whereas competences related to information and communication technology, and also leadership and ability to speak foreign languages, are revealed as weaknesses of university studies. Besides, several peculiarities have been identified according to the following fields of study: Humanities, Sciences, Engineering, Architecture and Economy and finally Fine Arts.